The Sweetest Fig - Van Allsburg, Chris (Boston : Houghton Mifflin, 1993)
After being given two magical figs that make his dreams come true, Monsieur Bibot sees his plans for future wealth upset by his long-suffering dog.
Sch Libr Jnl
Kirkus
Booklist
Publ Weekly
Keywords: Dreams -- Fiction; Magic -- Fiction; Dogs -- Fiction